2021
DOI: 10.1007/s13300-021-01153-4
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Insulin Glargine 300 U/ml in Comparison with Insulin Degludec 100 U/ml Evaluated with Continuous Glucose Monitoring in Adults with Type 1 Diabetes and Suboptimal Glycemic Control in Routine Clinical Practice: The OneCARE Study

Abstract: Introduction: Data regarding efficacy of second-generation basal insulins (BI) using continuous glucose monitoring (CGM) come from clinical trials. We evaluated the effectiveness of insulin glargine 300 U/ml (Gla-300) compared to insulin degludec 100 U/ml (IDeg-100) in terms of percentage of time in range (TIR); 70-180 mg/dl was obtained from CGM in suboptimally controlled patients with type 1 diabetes (T1D) in routine clinical practice. Methods: This observational, multicenter, cross-sectional study included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…However, the findings of the current study were in line with the results of some recent studies comparing the TDD between patients using insulin glargine 300 U/mL and those using insulin degludec 100 U/mL. These studies reported that there was no significant difference in the TDD between patients using either type of ultra-long-acting basal insulin analogs (51,52).…”
Section: Discussionsupporting
confidence: 92%
“…However, the findings of the current study were in line with the results of some recent studies comparing the TDD between patients using insulin glargine 300 U/mL and those using insulin degludec 100 U/mL. These studies reported that there was no significant difference in the TDD between patients using either type of ultra-long-acting basal insulin analogs (51,52).…”
Section: Discussionsupporting
confidence: 92%
“…To date, the OneCare 25 study is the only RWE study including CGM data for glycemic variability in people living with T1D who were switched from a first-generation basal insulin analog (Gla-100 or detemir) to either Gla-300 or iDeg-100. OneCare was an observational, retrospective, cross-sectional study in Spain analyzing 14 days of consecutive CGM use with data from the FreeStyle Libre device (Abbott), captured 3–24 months after the switch.…”
Section: Real-world Evidencementioning
confidence: 99%
“…Compared with OneCare, 25 COMET-T is a prospective study (vs retrospective), covers different basal insulins as the reference treatment (vs Gla-100 or iDeg-100), and different CGM devices available in clinical practice (vs FreeStyle Libre only). Furthermore, COMET-T covers an observational period of 24 weeks.…”
Section: Real-world Evidencementioning
confidence: 99%
“…The OneCare observational, retrospective cohort, cross-sectional, multicentre study compared the effectiveness and safety of Gla-300 versus Deg-100 over a four-week period [ 36 ] in adult patients with T1DM. Gla-300 and Deg-100 showed a significantly different percentage of time in the target glucose range (3.9–10 mmol/L, 70–180 mg/dL) at night (Gla-300 52.4% vs Deg-100 46.2%, p = 0.0182).…”
Section: Pharmacokinetic and Pharmacodynamic Profiles Of Gla-300mentioning
confidence: 99%
“…No significant differences were reported for HbA1c values between cohorts [ 35 ]. Overall, in this real-world setting, the safety and effectiveness of Gla-300 and Deg-100 were similar in sub-optimally controlled T1DM patients switching from the first-generation basal insulins [ 36 ].…”
Section: Pharmacokinetic and Pharmacodynamic Profiles Of Gla-300mentioning
confidence: 99%